TERTIARY EFL LEARNERS’ BARRIERS IN TRANSLATING INDONESIAN NEWS ITEM TEXT INTO ENGLISH AND VICE VERSA - Rachmawati Achadiyah (Universitas Wiralodra, 2024)
One of the major topics to be investigated in this study is translation. This is not particularly new and has been studied for many years. However, The proficiency of English as a foreign language is reflected by the quality of translation. Despite this, learners still claim that translating is a rigid activity to do, even if they had learned the four English skills and vocabulary. Therefore, it is exciting to be investigated. The present study tries to discover what aspects become the most barrier for learners when translating. 25 learners who took translation classes were involved in this study. The primary data was obtained through closed-ended questionnaire, Thus this study was descriptive quantitative. The result now provides three major causes; first, the inability of students to decide which sentence must translate literally and which sentence must not translate literally. Second, the inability of students to construct perfect grammatical sentences from both two languages, Indonesia and English, and the third was aggravated by the learner's inability to find the most equivalence words or phrases from Indonesia to English and vice versa, including collocation and idioms.